PENGISIAN BATERAI LI-ION DENGAN METODE CONSTANT CURRENT, CONSTANT VOLTAGE, CONSTANT CURRENT – CONSTANT VOLTAGE - Nur Putra, Andi Muhammad; Ramadhan, Gilang (Ensiklopedia of Journal, 2023)
One of the main components in the development of environmentally friendly electric-based vehicle technology is the battery. Battery technology is growing along with the significant growth rate of electric vehicles lately. The main issues concerning the use of batteries are limited capacity, long charging times, and safety issues such as battery temperatures that can rise rapidly during use and charging. A number of innovations have been made to overcome the battery charging problem, which is key to the development of electric vehicles. This paper uses three charging methods to present the charging process of lithium-ion batteries that are widely used in electric vehicles. The simulation process was conducted with a 16.7 kW test circuit that is designed to deliver a maximum charging current of 90 A. Test results have been presented where charging with the constant current constant voltage method can provide better charging behavior for the battery. It took 100 minutes to fully charge the battery, keeping the temperature below the maximum limit of 45OC.Keywords: Battery, Charging, Time, Temperature.